1978
DOI: 10.1172/jci109223
|View full text |Cite
|
Sign up to set email alerts
|

Iron uptake from rat plasma transferrin by rat reticulocytes.

Abstract: A B S T R A C T Fast and slow rat transferrins were isolated by isoelectric focusing and prepared in their di-and monoferric forms. A comparison of the rates of iron release between fast and slow diferric transferrins and between fast and slow monoferric transferrins when incubated with reticulocytes or injected in vivo showed no significant difference in the behavior of the two isotransferrin species. Reticulocyte uptake of diferric transferrin resulted in the removal of both iron atoms from the transferrin m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
27
0

Year Published

1980
1980
1992
1992

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“…Animals to be made iron deficient were placed at 4 weeks on a diet containing 4-8 mg of iron per kg of body weight, or alternatively were given an iron-deficient diet at 6 weeks of age and bled 2-3 ml four or five times over 2 weeks to accelerate iron depletion. Female rats to be iron-loaded were placed on a 1% carbonyl iron diet for >1 year with occasional reintroduction of a normal diet to maintain animals in good health (11).…”
mentioning
confidence: 99%
“…Animals to be made iron deficient were placed at 4 weeks on a diet containing 4-8 mg of iron per kg of body weight, or alternatively were given an iron-deficient diet at 6 weeks of age and bled 2-3 ml four or five times over 2 weeks to accelerate iron depletion. Female rats to be iron-loaded were placed on a 1% carbonyl iron diet for >1 year with occasional reintroduction of a normal diet to maintain animals in good health (11).…”
mentioning
confidence: 99%
“…There has been considerable discussion concerning the behavior of this protein in view of the chemical differences between its two iron binding sites (1). Our recent studies, however, have shown that iron loading of the binding sites is essentially a random process and the release ofiron on incubation with erythroid cells is an "all-or-none" phenomenon (2)(3)(4)(5). In addition, it was shown that iron delivery from the two monoferric transferrins is identical when they are incubated in vitro with reticulocytes or bone marrow cells (4,6) or injected in vivo into rabbits (7).…”
mentioning
confidence: 99%
“…The two separable and chemically distinct monoferric forms of transferrin (AS and AL) have been shown to have identical iron-donating capacities, both in animals and in humans (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). In addition, iron release from any form of transferrin to erythroid cells was found to be an "all or none" phenomenon, generating only apotransferrin (5)(6)(7)(8)(9)(10)(11).…”
Section: Resultsmentioning
confidence: 99%
“…A heterogeneous behavior of the plasma iron pool could lead to a selective release of iron from one site, a selective loading of the two sites, or a combination of these. Recent studies failed to reveal functional differences in iron release between the two sites (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Instead, a competitive advantage of difemc transferrin over the two monoferric forms in delivering iron was apparent (13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation